Chronic nitrogen additions fundamentally restructure the soil fungal community in a temperate forest. (October 2016) - Morrison, Eric W.; Frey, Serita D.; Sadowsky, Jesse J.; van Diepen, Linda T.A.; Thomas, W. Kelley; Pringle, Anne
Abstract: Fungi dominate the microbial biomass of temperate forest soils and are a key driver of ecosystem nutrient cycling. Chronic nitrogen (N) amendments frequently cause the accumulation of soil organic matter within soils, suggesting that elevated N disrupts decomposition by altering fungal communities. To link previously observed increases in soil organic matter with potential changes in the fungal community, we assessed the effects of soil N amendment on fungal community structure at a long-term N addition experiment at Harvard Forest (Petersham, MA, USA). A decline in the relative abundance of ectomycorrhizal fungi following long-term N addition was offset by an increase in the relative abundance of saprotrophs. Species richness and diversity of ectomycorrhizal fungi declined, while ascomycetes and saprotrophs responded positively to N enrichment. However, nitrophilic species included ectomycorrhizal as well as saprotrophic fungi, especially the ectomycorrhizal Russula vinacea, whose relative abundance increased from 10 to 37% of the entire community across N treatments. Two decades of soil N enrichment appears to have fundamentally altered the soil fungal community of this temperate forest.